2013
DOI: 10.1002/anie.201303883
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocyanative Cyclization and Three‐Component Cross‐Coupling Reaction between Allenes and Alkynes under Nickel Catalysis

Abstract: Vollgepackt mit Funktionalität: Der Schlüsselschritt in den Titelreaktionen mit Acetoncyanhydrin ist eine regioselektive Hydronickelierung von Allenen. Anschließende Carbometallierung des Alkins und reduktive Eliminierung ergaben cyanofunktionalisierte tetrasubstituierte Alkene in regio‐ und stereoselektiver Weise (siehe Schema; EWG=elektronenziehende Gruppe, Ts=p‐Toluolsulfonyl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…We have shown that these catalysts, in combination with chelating phosphine ligands (BINAP, dppf, Xantphos), provide active catalyst species that can be successfully applied to both C–S, and C–N, cross-coupling reactions. Other groups have also reported the effectiveness of nickel phosphine-phosphite or nickel phosphite complexes as catalysts. One limitation that we have noticed though is that these nickel diphosphine-phosphite or homoleptic nickel phosphite systems were sluggish as catalysts when used in some C–C bond forming reactions such as the Suzuki–Miyaura cross-coupling. To address this shortcoming, we surmised that using a monodentate NHC instead of a chelating diphosphine would lead to an appropriately active catalyst system, expecting that the σ-donor character of NHC ligands and the π-acidic phosphites would offer unique catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that these catalysts, in combination with chelating phosphine ligands (BINAP, dppf, Xantphos), provide active catalyst species that can be successfully applied to both C–S, and C–N, cross-coupling reactions. Other groups have also reported the effectiveness of nickel phosphine-phosphite or nickel phosphite complexes as catalysts. One limitation that we have noticed though is that these nickel diphosphine-phosphite or homoleptic nickel phosphite systems were sluggish as catalysts when used in some C–C bond forming reactions such as the Suzuki–Miyaura cross-coupling. To address this shortcoming, we surmised that using a monodentate NHC instead of a chelating diphosphine would lead to an appropriately active catalyst system, expecting that the σ-donor character of NHC ligands and the π-acidic phosphites would offer unique catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrofunctionalization of allenes mainly allowed the selective formation of C–N, C–O, and C–C bond. [ 2,3,5–8 ] The latter being performed through the addition of pronucleophiles such as malonates, [ 9–12 ] nitriles, [ 13–16 ] alkynes, [ 17–19 ] alkenes, [ 20–22 ] and aryl derivatives. The reaction of aromatic compounds with allenes, known as hydroarylation reaction, consists of adding an aryl moiety to a C–C double bond and constitutes a powerful tool to form a Csp 3 –Csp 2 bond in a regio‐ and stereoselective manner.…”
Section: Methodsmentioning
confidence: 99%
“…Sequential formation of a Ni-carbene intermediate (3a-2), followed by reductive elimination, gives 2a as a single isomer. The origin of the olefinic stereochemistry would be steric repulsion between the triisopropylsilyl (TIPS) and c-Hex groups to promote C-C bond rotation 35) in 3a-2 before reductive elimination from 3a-3 to form a C-CN bond (anti-carbocyanation).…”
Section: Hydrocyanative Cyclization Using Enyne and Allene-ynesmentioning
confidence: 99%